2008
DOI: 10.1111/j.1460-9568.2008.06343.x
|View full text |Cite
|
Sign up to set email alerts
|

Rac1 in cortical projection neurons is selectively required for midline crossing of commissural axonal formation

Abstract: Rac1 is a member of Rho family GTPases and regulates multiple cellular functions through actin cytoskeleton reorganization. During cerebral corticogenesis, Rac1 has been assumed to be involved in neuronal migration, neurite formation, polarization and axonal guidance. Here we show the specific role of Rac1, regulating midline crossing of commissural axons during cortical development by using cortex-restricted Rac1-knockout mice. In the knockout mice, Rac1 was eliminated from the beginning of corticogenesis exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
80
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 42 publications
8
80
1
Order By: Relevance
“…restricted Rac1-knock-out mice is not impaired (Kassai et al, 2008). Here, we showed that Rac1 signaling is essential for efficient migration of one of the largest population of neurons in the brain, CGNs.…”
Section: Neuronal Migration Requires Rac1 Functionmentioning
confidence: 84%
See 3 more Smart Citations
“…restricted Rac1-knock-out mice is not impaired (Kassai et al, 2008). Here, we showed that Rac1 signaling is essential for efficient migration of one of the largest population of neurons in the brain, CGNs.…”
Section: Neuronal Migration Requires Rac1 Functionmentioning
confidence: 84%
“…Rac1 and Rac3 are present in the nervous system (Didsbury et al, 1989;Bolis et al, 2003), and the expression of mutant Racs causes aberrant axon formation in mouse and chick neurons (Luo et al, 1996;Albertinazzi et al, 1998). By contrast, deletion of Rac3 or specific ablation of Rac1 in the mouse cortex does not affect axon growth (Corbetta et al, 2005;Chen et al, 2007;Gualdoni et al, 2007;Kassai et al, 2008). This suggests that axon growth may be independent of Rac activity.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Since Rac1 is an important signaling mediator of many classic axon guidance cues, including the netrin/DCC signaling pathway, [57][58][59][60] it was not so surprising to observe a complete absence of the anterior commissure in the brain of Rac1-deficient embryos. 55,61 Furthermore, the corpus callosal and the hippocampal commissural axons failed to cross the midline in Rac1-deficient embryos while there was also projection and defasciculation defects of the corticothalamic and thalamocortical axons. However, no defect in the axonal outgrowth of telencephalic neurons was observed in Rac1-deficient embryos but a reduction in cortical interneurons within the cortex indicated a defect in tangential migration.…”
Section: Cns Developmentmentioning
confidence: 99%